Metabolic syndrome is associated with worse prognosis in elderly patients with hepatocellular carcinoma - Huang, Junwei; Tao, Yiming; Yao, Jianguo; Song, Xiaorui; Li, Yiming; Yuan, Yiting (Frontiers in Oncology, 2025)
BackgroundMetabolic syndrome (MetS), a constellation of metabolic abnormalities such as obesity, hypertension, dyslipidemia, and insulin resistance, has been implicated in cancer progression. However, its impact on the prognosis of hepatocellular carcinoma (HCC) in elderly patients remains unclear. This study evaluates the relationship between MetS and survival outcomes in elderly patients undergoing hepatectomy for HCC.MethodsThis retrospective cohort study enrolled elderly HCC patients (≥65 years) who underwent hepatectomy at The First People’s Hospital of Tongxiang between January 2018 and December 2022. Patients were categorized into MetS and non-MetS groups based on diagnostic criteria by the Chinese Diabetes Society. Propensity score matching (PSM) was performed, yielding 166 matched pairs. Overall survival (OS) and recurrence-free survival (RFS) were analyzed using Kaplan-Meier curves and Cox proportional hazards models, adjusted for potential confounding factors.ResultsThe 5-year recurrence (57.2% vs. 41.0%, P = 0.02) and mortality (33.1% vs. 17.5%, P < 0.01) rates were notably higher among patients with MetS compared to those without. Multivariate Cox regression showed that MetS was independently associated with a 1.43-fold increased risk of recurrence (95% CI: 1.02-2.00; P = 0.04) and a 1.73-fold increased risk of mortality (95% CI: 1.08–2.77; P = 0.02). A dose-response relationship was observed: each additional MetS component was associated with a 1.55-fold increased risk of recurrence (95% CI: 1.31–1.83; P < 0.01) and a 1.73-fold increased risk of mortality (95% CI: 1.39–2.17; P < 0.01).ConclusionsMetS is associated with significantly worse survival outcomes in elderly HCC patients, with mortality risk escalating as the number of MetS components increases.